Tree cover assessment and terrestrial arthropod composition of the Philippine tarsier (Tarsius Carlito] syrichta) habitat in Balugo Falls, Brgy. Salvacion, Tacloban City - Colasito, Shaira Elaine M. (2019)
There are three extant species of tarsiers in the world: Tarsius for those found in Sulawesi, Cephalopachus in Sundaland, and Carlito in Greater Mindanao. Tarsius syrichta is the species of tarsier found in the Greater Mindanao faunal region comprised of Leyte, Samar, Maripipi, Biliran, Dinagat, Siargao, Bohol, and Mindanao. A primary assessment of Philippine tarsier (Tarsius syrichta) habitat and resource availability in Balugo Watershed, Brgy. Salvacion, Tacloban City, Leyte, through tree cover assessment and arthropod survey is the focus of the study. The tree cover was calculated using the basal area and a species richness assessment of captured and observed arthropods. The density of the arthropods and species of trees are disregarded in the paper.